2007
DOI: 10.1016/j.ophtha.2007.07.005
|View full text |Cite|
|
Sign up to set email alerts
|

Optic Nerve Head and Retinal Nerve Fiber Layer Analysis

Abstract: Objective-To evaluate the current published literature on the use of optic nerve head (ONH) and retinal nerve fiber layer (RNFL) measurement devices in diagnosing open-angle glaucoma and detecting progression. Results-There were no studies classified as having the highest level of evidence (level I). The ONH and RNFL imaging instruments reviewed in this assessment were determined to be highly effective in distinguishing eyes with glaucomatous visual field (VF) loss from normal eyes without VF loss, based on le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(25 citation statements)
references
References 62 publications
0
24
0
1
Order By: Relevance
“…in the primary visual cortex (V1) in response to appropriate stimuli [3]. There are numerous ophthalmological methods to determine neuronal reasons for impaired vision [4,5]. Among them, we can find quantification (1) of the retinal nerve fiber layer (RNFL) thickness; (2) of the optic nerve head morphology; (3) of visual field defects by perimetry; (4) of the spatial-temporal contrast sensitivity, and (5) of the visual evoked potential.…”
Section: Introductionmentioning
confidence: 99%
“…in the primary visual cortex (V1) in response to appropriate stimuli [3]. There are numerous ophthalmological methods to determine neuronal reasons for impaired vision [4,5]. Among them, we can find quantification (1) of the retinal nerve fiber layer (RNFL) thickness; (2) of the optic nerve head morphology; (3) of visual field defects by perimetry; (4) of the spatial-temporal contrast sensitivity, and (5) of the visual evoked potential.…”
Section: Introductionmentioning
confidence: 99%
“…These results are in general agreement with the specificity reported by the earlier authors for photographic and imaging criteria. 12 In contrast, the diagnostic performance of the Finnish guideline in the participants from Source 2 produced a high number of positives. Group 2 is not a conventional 'case or glaucoma' group and cannot be considered as the glaucoma group.…”
Section: Eyementioning
confidence: 97%
“…5 Time-domain OCT, first introduced in 1995, 6,7 has become widely used to obtain RNFL measurements in eyes with glaucoma. [8][9][10] Recently, advances in technology allowed the development of spectral-domain OCT (SD-OCT), which provides faster acquisition, better resolution, and improved visualization of retinal morphology. 8 By using the advanced technology of SD-OCT, the Cirrus HD-OCT acquires data about 70 times faster (27 000 vs 400 A-scans per second) and with better resolution (5 vs B10 mm of axial resolution in tissue) when compared to the first generation of OCT. 9,11 Furthermore, some studies have indicated that time-domain OCT requires pupil dilation for the acquisition of good quality images of the retina and RNFL.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Recently, advances in technology allowed the development of spectral-domain OCT (SD-OCT), which provides faster acquisition, better resolution, and improved visualization of retinal morphology. 8 By using the advanced technology of SD-OCT, the Cirrus HD-OCT acquires data about 70 times faster (27 000 vs 400 A-scans per second) and with better resolution (5 vs B10 mm of axial resolution in tissue) when compared to the first generation of OCT. 9,11 Furthermore, some studies have indicated that time-domain OCT requires pupil dilation for the acquisition of good quality images of the retina and RNFL. [11][12][13] Although the manufacturer of the Cirrus HD-OCT indicates that the images can be obtained without pupil dilation, there is no study in the literature investigating the effects of pupil dilation on the measurements obtained with this instrument.…”
Section: Introductionmentioning
confidence: 99%